2019
DOI: 10.1111/jnu.12529
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Prostate Cancer Screening by Men in Sub‐Saharan Africa: An Integrated Review

Abstract: Prostate cancer is a major sexual and reproductive health problem for men the world over. It remains an important public health concern in Western countries and an emerging malignancy in developing nations (Rawla, 2019). Ferlay et al. (2013) and Ervik and Asplund (2012) stated that prostate cancer is the second most common malignancy and the fifth leading cause of cancer mortality in men. By the year 2013, prostate cancer incidence and mortality in men had risen to 240,000 new cases and to more than 29,000 dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
3
34
0
1
Order By: Relevance
“…In the study, lack of knowledge on PC was reported as a major barrier to uptake of screening. This finding is corroborated with studies conducted among men in the Sub-Saharan African region and Kenya (8,9,15). Participation of men in screening is highly dependent on their knowledge about PC and the benefits of early detection.…”
Section: Discussionsupporting
confidence: 81%
“…In the study, lack of knowledge on PC was reported as a major barrier to uptake of screening. This finding is corroborated with studies conducted among men in the Sub-Saharan African region and Kenya (8,9,15). Participation of men in screening is highly dependent on their knowledge about PC and the benefits of early detection.…”
Section: Discussionsupporting
confidence: 81%
“…1,3 Studies on the uptake of screening show a lack of early-detection services and public awareness. 4,5 Accordingly, hospitalbased studies reveal that most patients present with symptomatic disease and are diagnosed at late stages. 6 African American and Afro-Caribbean race has been associated with a more aggressive form of PCa and poorer outcomes in comparison with other population groups.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review from Baratedi et al, similarly pointed towards lack of knowledge and a multitude of misconceptions about the disease. This study also identified lower education and socioeconomic status as barriers to prostate cancer screening on the patient level [ 43 ]. These factors are also known to influence the outcome of prostate cancer patients in general [ 44 ].…”
Section: Discussionmentioning
confidence: 99%